ANALISIS PENGUSAHA MENINGGALKAN MUAMALAH YANG HARAM: (Studi Fenomologi Pengusaha di Sumbersari Jember) - Misbahuzzulam; Abd.Muthalib; Khoirul Ahsan (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2023)
Business/entrepreneurship is one of the muamalah practices that the community often engages in, but unfortunately many of them are still involved with the problem of usury for capital. Besides aiming to find out someone's life experience in business. This research was also carried out to explore the causes, namely starting a business, starting capital, constraints when running a business using usury money and the benefits of leaving usury. The research focused on small-scale businesses in Sumbersari, Jember Regency using a qualitative approach. This research uses a type of case study research. A case study is a process of examining, understanding, explaining and testing comprehensively, intensively and in detail about a natural setting of individuals, groups, organizations, institutions, certain cultures, parties, events, certain documents, and so on. Keywords: muamalah; unclean; usury.